Greywater biodegradability and biological treatment technologies: A critical review. (July 2021) - Khalil, Mostafa; Liu, Yang
Abstract: Treatment of greywater (wastewater without fecal contamination) for reuse can play an important role in reducing global water scarcity, especially in arid and semi-arid regions. Biological methods are commonly used to treat greywater, but the presence of surfactants and a nutrient deficiency in some greywaters have negative effects on the biodegradability of greywater components. Previously studied aerobic and anaerobic biological greywater treatment technologies include the sequencing batch reactor (SBR), the membrane bioreactor (MBR), rotating biological contactors (RBCs), the moving bed biofilm reactor (MBBR), and the upflow anaerobic sludge blanket (UASB). Surfactants used in homecare and cosmetics industry are primarily biodegraded under aerobic conditions. On the other hand, the surfactant linear alkylbenzene sulphonate (LAS) might inhibit anaerobic biodegradation. Further, dark greywater (water drained from kitchen sinks, dishwashers, washing machines) has sufficient nutrient concentrations needed for aerobic treatments, while light greywater (water drained from bathing, showering, hand washing) requires nutrient supplementation to enhance aerobic biodegradability. Thus, a careful characterization of the greywater to be treated must be performed before the biological treatment technology is chosen. The effects of surfactants on greywater treatment from the perspectives of aerobic and anaerobic biodegradability, nutrient addition, and treatment technologies are reviewed. Graphical abstract: Image 1 Highlights: Roles of surfactants biodegradability and nutrient requirements in biological greywater treatment were reviewed. Surfactants are biodegradable under aerobic conditions, but are recalcitrant for anaerobic biodegradation. Detailed characterization of grey water contaminants should be conducted for selecting biological treatment system.